Accelerating Agricultural Productivity and Marketing for Rural Transformation in Nigeria - Ogbeide-Osaretin , Evelyn Nwamaka; Ozougwu , Ben; Ebhote , Oseremen (Asian Journal of Agriculture and Rural Development, 2019)
This study examined the essential factors required to drive agricultural productivity and marketing towards enhancing rural transformation. Nigeria data on Total Factor Productivity (TFP) generated using the Solow’s residual approach, quality of labour force captured by different educational levels and health status, availability of credit, and the role of female gender among others were used for the period between1981-2016. Autoregressive distributed lag method was employed as no existence of long-run association was found among variables confirmed by the bound testing result. Findings showed that the female labour force is positively significantly related to TFP. Educational levels of labour were positively but insignificantly related to TFP except the primary educational level. Life expectancy rate was significantly negatively related to TFP. We thus recommended among others that female access to education and credit be enhanced to improve the female labour agricultural productivity, enhances the rural secondary and tertiary educational levels as well as increase in investment in farmers’ health status.